2017
DOI: 10.1039/c7cp02229h
|View full text |Cite
|
Sign up to set email alerts
|

High cross-plane thermoelectric performance of metallo-porphyrin molecular junctions

Abstract: aWe investigated the thermoelectric properties of flat-stacked 5,15-diphenylporphyrins containing divalent metal ions Ni, Co, Cu or Zn, which are strongly coordinated with the nitrogens of pyridyl coated gold electrodes. Changing metal atom has little effect on the thermal conductance due to the phonons.The room-temperature Seebeck coefficients of these junctions are rather high, ranging from 90 mV K À1for Cu, Ni and Zn-porphyrins to À16 mV K À1 for Co-porphyrin. These values could be further increased by lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…To address the problem of increasing the thermoelectric performance of organic molecules, Finch et al 10 demonstrated theoretically that large values of the Seebeck coefficient could be obtained by creating transport resonances and anti-resonances within the HOMO-LUMO gap and tuning their energetic location relative to the Fermi energy. Following these pioneering works, several experimental [11][12][13][14][15][16][17][18][19][20] and theoretical studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34] have attempted to probe and improve the thermoelectric performance of single molecules. However, progress has been hampered by the additional complexity of thermoelectric measurement set-ups, because unlike measurements of single-molecule conductance, Seebeck measurements require additional control and determination of temperature gradients at a molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…To address the problem of increasing the thermoelectric performance of organic molecules, Finch et al 10 demonstrated theoretically that large values of the Seebeck coefficient could be obtained by creating transport resonances and anti-resonances within the HOMO-LUMO gap and tuning their energetic location relative to the Fermi energy. Following these pioneering works, several experimental [11][12][13][14][15][16][17][18][19][20] and theoretical studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34] have attempted to probe and improve the thermoelectric performance of single molecules. However, progress has been hampered by the additional complexity of thermoelectric measurement set-ups, because unlike measurements of single-molecule conductance, Seebeck measurements require additional control and determination of temperature gradients at a molecular scale.…”
Section: Introductionmentioning
confidence: 99%
“…They further demonstrate such transmission system can operate with large power output and efficiencies close to the Curzon–Ahlborn limit. Noori et al recently investigated the influence of metal ions on the thermoelectric properties of flat‐stacked 5,15‐diphenylporphyrins containing divalent metal ions Ni, Co, Cu or Zn. Their calculations show that changing the metal atom has little effect on the thermal conductance due to the phonons, while the room‐temperature Seebeck coefficients of these junctions are high, ranging from 90 µV K −1 for Cu, Ni, and Zn‐porphyrins to −16 µV K −1 for Co‐porphyrin.…”
Section: Thermoelectric Properties Of Molecular Junctionsmentioning
confidence: 99%
“…Porphyrins have been used to develop artificial receptors that are used to recognize molecules 12 and to develop new chiral catalysts for asymmetric synthesis. 1315 They have also been used to explore biologically important response mechanisms such as photosynthesis 16 and P450 catalyst 17 oxidation–reduction reactions as well as stereochemical research. Porphyrins are also considered as attractive molecules in many respects.…”
Section: Introductionmentioning
confidence: 99%
“…Ethidium bromide, acridine orange, methylene blue, Ru­(II) complex, porphyrin, and small molecules are often used to understand the structure and properties of DNA through their interactions with drug–DNA and protein–DNA. The study of the interaction between porphyrins and DNA is continuously gaining interest. Porphyrins have been used to develop artificial receptors that are used to recognize molecules and to develop new chiral catalysts for asymmetric synthesis. They have also been used to explore biologically important response mechanisms such as photosynthesis and P450 catalyst oxidation–reduction reactions as well as stereochemical research. Porphyrins are also considered as attractive molecules in many respects.…”
Section: Introductionmentioning
confidence: 99%